Reading symbols and mythical landscape in the "Tambunan Dusun Origin Myth" of North Borneo - Low, Kok On (Penerbit Universiti Sains Malaysia, 2006)
This paper concerns reading symbols that had appeared in the “Tambunan Dusun Origin Myth” published in the Journal of Malaysia Branch Royal Asiatic Society (JMBRAS) by Williams (1960). As Campbell (1988: 5) said, “We should read myths. They teach us that we can turn inward, and we will begin to get the message of the symbols. Read other people’s myths, not those of your own religion, because you tend to interpret your own religion in terms of facts—but if you read the other one, you begin to get the message.” In other words, myth is a manifestation of symbolic images. The symbolic field is based on the experiences of people in a particular community, at that particular time and place.